A diplomat in the Revolta da Armada (brazilian naval revolt): political impressions and the role of Count of Paço D’Arcos (Tempo e Argumento, 2011)
The first diplomat that represented Portugal in the Brazilian Republic was Carlos Eugênio Corrêa da Silva, the Count of Paço D’Arcos. His Diplomatic Mission took place from 2 June 1891 to 20 November 1893. In his reports about the Brazilian political situation, arguments on social order defense and military hierarchy are recurrent, especially during the Armed Forces Insurrection. This article proposes to study diplomatic forces in order to understand the impressions and actions of this diplomat during this conflict.
Keywords: Count of Paço D’Arcos; diplomacy; Brazil and Portugal; politics; regional insurrections